Enhancing Teacher Competence in the Use of Learning Media through Academic Supervision - Handayani, Fransisca Heny; Samad, Abdul; Arif, Muhammad Ridwan (Newinera Publisher, 2024)
Academic supervision has a significant impact on teachers' abilities in developing learning processes, including planning, implementation, and assessment of learning. This study aims to identify and analyze efforts to enhance teacher competence, as well as the inhibiting and supporting factors in the use of learning media through academic supervision at SDN 020 Penajam. The method used is descriptive qualitative, utilizing interview techniques with teacher informants at SDN 020 Penajam. Data analysis techniques employ the interactive model of Miles and Huberman. The results show that the role of the school principal as an academic supervisor is substantial and helps teachers improve their competence in using learning media in the classroom. Despite technical obstacles such as limited network access, the enthusiasm and commitment of the supervisor in guiding and motivating teachers are supportive factors in efforts to enhance teacher competence in using learning media at SDN 020 Penajam.